Arachidonic acid supplementation modulates blood and skeletal muscle lipid profile with no effect on basal inflammation in resistance exercise trained men. (January 2018) - Markworth, James F.; Mitchell, Cameron J.; D'Souza, Randall F.; Aasen, Kirsten M.M.; Durainayagam, Brenan R.; Mitchell, Sarah M.; Chan, Alex H.C.; Sinclair, Andrew J.; Garg, Manohar; Cameron-Smith, David
Abstract: Arachidonic acid (ARA), an omega-6 polyunsaturated fatty acid (PUFA), is the metabolic precursor to the eicosanoid family of lipid mediators. Eicosanoids have potent pro-inflammatory actions, but also act as important autocrine/paracrine signaling molecules in skeletal muscle growth and development. Whether dietary ARA is incorporated into skeletal muscle phospholipids and the resulting impact on intramuscular inflammatory and adaptive processes in-vivo is not known. In the current study, resistance trained men (≥1 year) received dietary supplementation with 1.5 g/day ARA (n=9, 24 ± 1.5 years) or placebo (n=10, 26 ± 1.3 years) for 4-weeks while continuing their normal training regimen. Plasma and vastus lateralis muscle biopsies were collected in an overnight fasted state at baseline and week 4. ARA supplementation increased plasma content of ARA and gamma-linolenic acid, while decreasing relative abundance of linoleic acid, eicosapentaenoic acid, and dihomo-gamma-linolenic acid. In skeletal muscle, ARA and dihomo-gamma-linolenic acid content increased, whereas alpha-linolenic-acid was reduced. Compared to placebo, ARA supplementation reduced circulating platelet and monocyte number, and decreased the mRNA expression of the immune cell surface markers; neutrophil elastase/CD66b and interleukin 1-beta, in peripheral blood mononuclear cells. In muscle, ARA supplementation increased mRNA expression of the myogenic regulatory factors; MyoD and myogenin, but had no effect on a range of immune cell markers or inflammatory cytokines. These data show that dietary ARA supplementation can rapidly and safely modulate plasma and muscle fatty acid profile and promote myogenic gene expression in resistance trained men, without a risk of increasing basal systemic or intramuscular inflammation.